PRELIMINARY APPRAISAL OF THE PRAWN FISHERY OF KERALA - Banerji, S K; Chakraborti, D (Indian Journal of Fisheries, 2011)
A preliminary appraisal of the relation between fishing effort and catch of prawns in the Kerala waters has been made, using the prawn catch data available with the Central Marine Fisheries Research Institute and of the medium-sized vessels of the Government of India and the Indo-Norwegian Project operating along the Kerala coast from 1957 to 1969. The decline in catch per unit effort and the decline in the mean size of prawns in the commercial catches of Kerala are not signs of over-fishing but are indications of an expanding fishery. The analysis shows that very little increase in the catch will result even when the fishing effort is increased substantially and the immediate need is to stabilise the production at its present level.